Metacognitive Awareness and Its Effect on Reading Comprehension among Intermediate ESL Students - Nazar, Sajida; Rashid, Haroon ur (Pakistan Languages and Humanities Review, 2025)
The aim of this study is to provide a detailed analysis of the effectiveness of metacognitive strategies on reading comprehension skills among intermediate students. Reading comprehension plays pivotal role in academic achievements; however, many students face challenges like; extracting relevant information, summarizing text, and vocabulary issues. In order to access these issues a quasi-experimental research approach is adopted, which involves pre and post-tests assessments of control and experimental groups. In the intervention phase, the control groups were taught through traditional method, while the experimental groups were taught using metacognitive strategies. T-test was used to find the differences among both the groups through statistical means. The results show that after the intervention phase, experimental group showed significant improvement. Hence, it was devised from the results that metacognitive strategies should be applied to improve reading comprehension skills, instead of teaching traditionally. English language teachers should include metacognitive strategies in their lesson plans to improve reading comprehension skills.